Alaska Milk Corporation - Lozada, Salvacion G. (Animo Repository, 1998)
An industry as defined by Michael Porter, is a group of firms producing products that are close substitutes for each other and it satisfy the same needs and wants. Alaska milk Corporation exists in the food processing industry, specifically milk production, their main line of business. The firms in this industry processed consumer foods for food consumption.